AKTIVITAS ANTIOKSIDAN EKSTRAK DAUN KENIKIR (Cosmos caudatus Kunth) DENGAN BERBAGAI METODE EKSTRAKSI (ANTIOXIDANT ACTIVITY OF LEAVES EXTRACT OF KENIKIR (Cosmos caudatus Kunth) WITH VARIOUS EXTRACTION METHODS) - Ari Widiyantoro; Harlia Harlia (Indonesian Journal of Pure and Applied Chemistry, 2020)
Cosmos caudatus Kunth is a vegetable plant that is often used as a food ingredient and traditional medicine. This study aims to determine the antioxidant activity of C. caudatus Kunth leaves extract obtained by a variety of extraction methods. The antioxidant activity test was carried out using the DPPH method. The results showed that the yield of C. caudatus Kunth leaves extract by maceration method (10.98%) was higher than the percolation (7.28%) and soxhletation (8.22%). The antioxidant activity (IC50) of the macerated extract (12.5 ± 0.3 µg/mL) was also higher than the percolated extract (16.8 ± 0.2 µg/mL) and soxhletation (18.8 ± 0.2 µg/mL). The macerated extract showed the highest antioxidant activity because it contained many secondary metabolites such as flavonoids and phenolics.